HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN PROKRASTINASI AKADEMIK DI KALANGAN MAHASISWA DALAM MENYELESAIKAN SKRIPSI - Hendrik Tuaputimain; Victor Tutupary (IAKN Ambon, 2021)
This study aims to (1) describe social support and academic procrastination; and (2) knowing the relationship between social support and academic procrastination. Both are used to measure how big the impact is on Ambon City students in completing their final assignment. This study uses a survey research method with the aim of explanation to explain the relationship between variables through hypothesis testing. The research subjects were 90 people who were taken by accidental sampling. Data was collected using a questionnaire, which had previously been tested for validity and reliability. All data were analyzed with product moment correlation. The results showed that (1) the value of the correlation coefficient was 0.305 and p was 0.003 (p <0.05), which means that there is a negative relationship between social support from friends and academic procrastination in completing thesis for students.